The Effect of Resilience and Digital Capabilities on Students’ Adaptability to Change Moderated by Organizational Learning - Hartanti, Jahju; Winarno, Adi; Prayogo, Prayogo; Charamba, Erasmos (FKIP Universitas Lampung, 2024)
Exploring Moderating Role of Organizational Learning in Enhancing Adaptability to Change Through Resilience and Digital Capabilities. Objective: To determine the effect of final year student resilience and digital capabilities on adaptability to change for technology advancement which is moderated by organizational learning. Method: This research was done using a quantitative approach with a survey method. The study population were final-year students from various faculties at a public university, the sample tehnique was random sampling and the number of selected samples was 300 respondents. Questionnaires were used to collect data from research participants. The data were analyzed using moderate regression analysis (MRA) using SPSS. Findings: Resilience has a positive and significant effect on adaptability to change, digital capabilities have a positive and significant effect on adaptability to change. Organizational learning moderates the influence of resilience on adaptability to change. Furthermore, the organizational learning also moderates the effect of digital capabilities on adaptability to change. Conclusion: These findings imply that HEI prioritize programs that bolster students' resilience and digital skills to improve adaptability to change. Organizational learning should be recognized as a key factor that strengthens the impact of resilience and digital skills on adaptability Keywords: adaptability to change, digital capability, higher education institution, organizational learning, resilience.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024108